Morphological Features of Uzbek Dialects - Raimberdiyeva , Sarvinoz; Ergasheva , Oydinaxon (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article comprehensively analyzes the morphological features found in regional dialects of the Uzbek language. During the study, the formal and functional changes of plural, possessive, conjugation and verb tense suffixes used in Uzbek dialects are highlighted on the basis of examples. Also, the morphological differences between the literary Uzbek language and various regional dialects are studied on the basis of comparative analysis, and their formation factors, historical roots and linguistic significance are revealed. The article separately considers the system of morphological units found in the dialects of the Karluk, Kipchak and Oghuz groups of the Uzbek language, and their specific features and impact on the literary language are substantiated by scientific evidence. In addition, the reduction of suffixes in dialects, the transformation of morphological forms as a result of phonetic changes, as well as the features of some ancient grammatical forms were studied.